Metabolic changes associated with COVID-19 in patients admitted to the intensive care unit of a university hospital (Research, Society and Development, 2023)
Objective: To evaluate the relationship between laboratory parameters and the clinical outcome of patients with COVID-19 admitted to an intensive care unit of a university hospital. Methodology: Observational, retrospective, descriptive, comparative and quantitative study, ethically approved, carried out in the intensive care unit of a university hospital operating during the COVID-19 pandemic, carried out through an analysis of laboratory parameters present in the electronic medical records of infected patients by coronavirus, associating them with clinical outcomes and employing a statistical evaluation using the unpaired Student's T test to evaluate the mean and standard error of the mean of the parameters and application of the Receiver Operating Characteristic Curve (ROC) test to identify cutoff points more sensitive and specific parameters that could associate them with the outcome of death, considering significance p